Nutrient stocks and phosphorus fractions in mountain soils of Southern Ecuador after conversion of forest to pasture - Makeschin, F. (2012)
Understanding pasture degradation processes is the key for sustainable land management in the tropical mountain rainforest region of the South Ecuadorian Andes. We estimated the stocks of total carbon and nutrients, microbial biomass and different P fractions along a gradient of land-uses that is typical of the eastern escarpment of the Cordillera Real i.e., old-growth evergreen lower montane forest, active pastures (17 and 50 years-old), abandoned pastures 10 and 20 years old with bracken fern or successional vegetation. Conversion of forest to pasture by slash-and-burn increased the stocks of SOC, TN, P and S in mineral topsoil of active pasture sites. Microbial growth in pasture soils was enhanced by improved availability of nutrients, C:N ratio, and increased soil pH. Up to 39 % of the total P in mineral soil was stored in the microbial biomass indicating its importance as a dynamic, easily available P reservoir at all sites. At a 17 years-old pasture the stock of NH4F extractable organic P, which is considered to be mineralisable in the short-term, was twice as high as in all other soils. The importance of the NaOH extractable organic P pool increased with pasture age. Pasture degradation was accelerated by a decline of this P stock, which is essential for the long-term P supply. Stocks of microbial biomass, total N and S had returned to forest levels 10 years after pasture abandonment; soil pH and total P 20 years after growth of successional bush vegetation. Only the C:N ratio increased above forest level indicating an ongoing loss of N after 20 years. Soil nutrient depletion and microbial biomass decline enforced the degradation of pastures on the investigated Cambisol sites.